Termination of Employment of PT. Lotte Mart Indonesia - Sunandar, Sunandar; Tahir, Palmawati; Arifinal, Mochamad (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
The purpose of this study is to analyze the decision of the panel of judges in deciding Case Number 69/Pdt.Sus-PHI/2020/PN Jkt.Ps based on the Labor Law and find legal protection efforts and rights obtained by workers at PT. Lotte Mart Indonesia against Unilateral Layoffs. This study uses normative legal research methods with statutory and conceptual approaches supported by primary and secondary legal materials and uses qualitative analysis techniques in order to be able to see the problems that occur in the field. The results of this study indicate that the case of PT. Lotte Mart Indonesia is one of the cases of unilateral layoffs that violate the provisions of the Labor Law. The absence of clear sanctions in the law provides an opportunity for companies to unilaterally lay off their employees. For workers who are dismissed unilaterally, they are required to obtain legal protection regulated in the Manpower Law as the President's commitment to improving quality in the economic sector. Companies that carry out layoffs unilaterally also need to receive appropriate sanctions as a result of violating the law and not fulfilling the rights of citizens guaranteed by the constitution.